ANALISIS PERBAIKAN KUALITAS INJECTION PART DENGAN PENDEKATAN LEAN SIX SIGMA: (ANALYSIS OF QUALITY INJECTION PART IMPROVEMENT WITH LEAN SIX SIGMA APPROACH) - Miftakul Huda (EKOMABIS: Jurnal Ekonomi Manajemen Bisnis, 2020)
Lean Six Sigma is a collective approach, which uses various techniques and tools for quality improvement. Here, Lean Six Sigma methodology was applied to a small injection molding unit (which can be taken as representative of small and medium-size industries) manufacturing casing of electronics part. The DMAIC (Define, Measure, Analyze, Improve and Control) approach of Lean Six Sigma was applied to reduce the rejection rate of the casing (child part of an electronic product) by changing setting parameters: mold temperature, injection pressure and injection speed in the injection mold process. The statistical techniques such as DOE full factorial experiment, and process capability analysis were done to finding the process capability before and after the Lean Six Sigma implementation. After implementing the Lean Six Sigma DMAIC approach it was found that injection molding firms can increase their profit by increase yield rate and deleting rejection rate of casing part. Lean Six Sigma implementation increase the process sigma level from 4,3σ to 4,7σ by a reduction in casing flow mark variation and transparency. This increase in sigma level will give defect cost reduction to the industry which is a good figure for such an industry. Abstrak Lean Six Sigma adalah pendekatan kolektif, yang menggunakan berbagai teknik dan alat untuk peningkatan kualitas. Di sini, metodologi Lean Six Sigma diterapkan pada unit injection molding kecil (yang dapat dianggap mewakili industri ukuran kecil dan menengah) manufaktur casing part. Pendekatan DMAIC (Define, Measure, Analyze, Improve and Control) Lean Six Sigma diterapkan untuk mengurangi tingkat penolakan casing part (bagian anak dari produk elektronik) dengan mengubah tiga setting parameter: suhu mold, tekanan dan kecepatan injection dalam proses cetakan injeksi. Teknik statistik seperti DOE full factorial experiment,dan analisis kemampuan proses dilakukan untuk menemukan kemampuan proses sebelum dan sesudah implementasi Lean Six Sigma. Setelah menerapkan pendekatan Lean Six Sigma DMAIC ditemukan bahwa perusahaan injection molding dapat meningkatkan keuntungannya dengan menaikan yield rate dengan mengendalikan tingkat penolakan casing part. Implementasi Lean Six Sigma meningkatkan tingkat sigma proses dari 4,3σ menjadi 4,8σ dengan mengurangi variasi flow mark dan transperancy. Kenaikan tingkat sigma ini akan memberikan pengurangan biaya akibat cacat ke industri yang merupakan contoh yang baik untuk industri semacam ini.